Fabrication of microstructured yttria-stabilized zirconia electrolyte surface using centrifugal molding for high-performance solid oxide fuel cells. Issue 1 (2022) - Nagato, Keisuke; Nagai, Kohei; Okamura, Toshihide; Tomizawa, Morio
Abstract: This study replicated the surface of yttria-stabilized zirconia (YSZ) microstructures by centrifugal filling to improve the performance of solid oxide fuel cells. A slurry with YSZ nanoparticles were filled with centrifugal force in polymer replica mold, solvent dried, and then transferred and sintered onto a bulk YSZ electrolyte plate. 3 m-pitch pillar structure was successfully replicated with a centrifugal acceleration of 2, 500 G, and the polarization resistance of the electrodes was reduced by approximately 25%. Similarly, a line-and-space structure was formed to investigate the structure dependence, and resistance reduction was confirmed. Furthermore, a distribution relaxation time analysis confirmed that the reduction in resistance was due to decreasing tortuosity factor of YSZ.